Sensitivity Analysis of AuNP-Functionalized D-Shaped Optical Fiber SPR Sensor Using Agricultural Media - MAZLAN, MUHAMMAD ZELMY HATIM; Awang, Noor Azura (Enhanced Knowledge in Sciences and Technology, 2026)
Agricultural water quality monitoring requires a robust and sensitive sensing platform capable of detecting changes in environmental media. This study presents the fabrication and characterization of a D-shaped optical fiber surface plasmon resonance (SPR) sensor functionalized with gold nanoparticles (AuNPs). The sensor performance was evaluated using carrot extract solutions with varying concentrations (20%–100%) as a model agricultural medium to induce refractive index variations at the sensing interface. Experimental results show a systematic red shift in the SPR resonance wavelength from 1546.944 nm to 1546.979 nm as the extract concentration increases, corresponding to a maximum wavelength shift of 107 nm. The observed response confirms the high sensitivity of the AuNP-enhanced D-shaped optical fiber to refractive index changes in liquid agricultural samples. This discovery establishes a reliable refractive index sensing platform that can serve as a basic structure for future functionalization towards the detection of selected heavy metals, such as lead (Pb²⁺), in agricultural applications.